Profile of patients with renal transplant - a cross-sectional study - Ana Luisa Brandão de Carvalho Lira; Jaqueline Galdino Albuquerque; Marcos Venícios de Oliveira Lopes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The renal transplant is the majority choice treatment of the patients with chronic renal deficiency. Such fact it owes to the appearance of powerful immunosuppressive drugs and to the rigorous criterion in the donors' choice. It aimed identify patients' renal transplanted profile. Quantitative study of cross-sectional, exploratory and descriptive type, performed in hospital academic of Fortaleza, between months from december/2004 to april/2005. The data collection instrument was an interview script. The results showed that most was of the masculine sex, with average 40 year and 51,7% lived with companion. The average family income was of 4,44 minimum wages and most was retired. We realize that the profile study of these patients provided us a reality larger knowledge, contributing to address the ambulatory assistance to this clientele.